Proteome Profile Changes Induced by Heterologous Overexpression of Mycobacterium tuberculosis-Derived Antigens PstS-1 (Rv0934) and Ag85B (Rv1886c) in Mycobacterium microti - Viridiana García-Ruiz; Patricia Orduña; Antonia I. Castillo-Rodal; Teresa J. Flores-Rodríguez; Yolanda López-Vidal (Biomolecules, 2022)
The development of new tuberculosis vaccines remains a global priority, and recombinant vaccines are a frequently investigated option. These vaccines follow a molecular strategy that may enhance protective efficacy. However, their functional differences, particularly with respect to glycosylation, remain unknown. Recent studies have shown that glycosylation plays a key role in the host-pathogen interactions during immune recognition. The aim of this study was to determine the differences in the glycosylation profiles of two recombinant strains of Mycobacterium microti, overexpressing Ag85B (Rv1886c) and PstS-1 (Rv0934) antigens of M. tuberculosis. For each strain, the glycosylation profile was determined by Western blotting with lectins. The results showed the presence of mannosylated proteins and evidence of linked sialic acid proteins. Interestingly, different proteome and glycoproteome profiles were observed between the two recombinant strains and the wild-type strain. We have shown here that the construction of the recombinant strains of M. microti has altered the proteome and glycosylation profiles of these strains, leading us to ask what impact these changes might have on the immune response.